Cliff Green interviewed by Hazel de Berg in the Hazel de Berg collection - Green, Cliff, 1934-2020; De Berg, Hazel, 1913-1984. (1980)
Green speaks of his work as a writer of television dramas ; writing an adaptation of the Norman Lindsay novel "Half way to anywhere" ; the film "Picnic at Hanging Rock" ; his work on various other film scripts ("Break of day", "Summerfield"). Green describes his method of work and speaks of his most adventurous project: "Burn the butterflies", a script for television ; he describes the problems involved when writing for television and speaks of forthcoming projects.
Digital master available
Transcript available (47 p.)
Keywords: Green, Cliff, -- 1934- -- Interviews; Picnic at Hanging Rock; Screenwriters -- Australia -- Interviews; Television writers -- Australia -- Interviews